Active vibration control: A graphical approach for optimal distribution. (1st June 2019) - Wang, Jiqiang
Highlights: A graphical method is proposed for optimal vibration distribution. Existence and optimality of feasible controllers are addressed. Performance limit of controllers is obtained. Influence of constraints on optimal solutions is delineated. Abstract: A number of design methodologies have been proposed for active control of vibrations. Most of the approaches proceed with formulating control design as optimization problems. These optimization-based methods are powerful and easy to use since numerical algorithms are usually available for finding solutions. However, the available methods have to be significantly modified to answering questions such as controller existence and achievable performance etc. This paper proposes a performance-limit-oriented solution developed for the problem of optimal distribution. A graphical approach is utilized for representation of the solutions. A number of important results upon existence of feasible controllers, optimality and performance limit of controllers, controller synthesis, as well as constraints handling are obtained; the puzzling issue of compromise between performance indices is resolved; the influence of constraints on optimal solutions are developed within the same graphical framework. This leads to a systematic design methodology to active vibration control for optimal distribution. The theoretical results are demonstrated through numerical examples and real time simulations.